The One show.
Here's something we all know: winning a one show pencil is damn hard. It takes a lot of unreturned phone calls, eroded relationships, rushed lunches, broken promises, guts, mistakes, and hours of fluorescent light to reach that level of excellence. Even a merit is freaking amazing. With so much talent on each page, the One Show is probably the hardest book to write. So, if your name is here, please accept my most sincere congratulations! You are raising the creative standard in every corner of the world; and that comes with the global recognition, prestige, and praise that you deserve. But I also want to extend my congratulations to all of those who didn't make it into the book. You ma not have won this year, but thanks to you, everyone did. You see, The One Club doesn't make money. It makes careers. It makes diversity actually happen. It makes underprivileged kids get a real shot at advertising greatness. It makes the past, present and the future promising. Because every penny goes back into making our industry better in every possible way. In a profession that gives all of us so much, The One Club is there to give back. Winning a Pencil propels career; and not winning propels an entire industry. Talk about return on investment.